Polyphenols for Cancer Treatment or Prevention - Karen Bishop (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Polyphenols are commonly found in fruits and vegetables, and have been suggested to have protective effects against chronic diseases, such as cancers. They are a diverse group of molecules, many of which possess antioxidant, anti-inflammatory, epigenetic, drug sensitization, and/or modulation of xenobiotic metabolizing enzyme properties. However, there is mixed evidence regarding their protective effects with respect to various cancers. Some of this controversy may be due to the combination of polyphenols administered, synergistic effects of accompanying compounds, bio-accessibility, bioavailability, effect of gut microbiota, and the type of cancer investigated. The purpose of this Special Issue is to present the recent evidence for the effect of polyphenol intake on cancer, as well as mechanisms of action. This Special Issue, entitled "Polyphenols for Cancer Treatment or Prevention", welcomes manuscript submissions of original research, meta-analyses, or reviews of the scientific literature. Authors should focus their manuscripts on polyphenol bioactives or dietary patterns naturally rich in polyphenols that have been identified and used for the prevention and or treatment of cancer.